'République and laïcité': What is at stake in contemporary France?. (May 2016) - Gaudin, Philippe
How should one define the republican democratic and ' laïque ' spirit in both the most concise and effective manner, as well as that most suited to the French case? The republican spirit resides without doubt in refusing submission to any single individual whoever that individual may be. The democratic spirit does not consist of decreeing the sovereignty of the people, but in developing formal modalities of political life allowing the people not to be divested of it. The ' laïque ' spirit rejects all distinctions concerning the nature and rights of citizens; it also equally rejects religious laws being imposed over political law.